Role of Computed Tomography in the Evaluation of Space Occupying Lesions in the Liver with Cytopathological Correlation (Journal of Chittagong Medical College Teachers' Association, 2020)
Background: The widespread availability of non-invasive radiological and diagnostic imaging techniques significantly contributes to detect space occupying lesions in the liver.  So the objective of the present study is to establish diagnostic usefulness of computed tomography in the evaluation of space occupying lesions in the liver.Materials and methods: It is a cross sectional study done in the Department of Radiology and Imaging, Chittagong Medical College Hospital, Chattogram, during a six months periods. Patients having suspected hepatic space occupying lesions (Clinical / on ultrasonography / High serum a-fetoprotein level) attending Department of Radiology and Imaging, were the study patients. A total of 70 patients of space occupying lesions in the liver were recruited. All CT scans were performed with a 16 slice multidetector Philips MX whole body scanner using standard technical parameters. Age, sex, clinical presentation, physical examination, CT evaluation and cytopathological findings were noted.   Results:  It was observed that majority (42.9%) patients had belonged to age £ 40 years. The mean age was 45.7 ± 11.6 years. Almost two third 42(60.0%) patients were male. Two third (62.9%) patients came from middle class. It was observed that 44(62.9%) patients had enlarged liver, 36(51.4%) patients had multiple  number of lesions, the mean size of lesion had 5.0±3.2 cm,  36(51.4%) patients had lesions in  both lobe of liver, 38(54.3%) patients had well defined margin of mass, 44(62.8%) patients had hypodense lesion in pre contrast CT, 28(40.0%) patients had  marked  enhancement in post contrast CT, 55(78.6%) patients  had lesion enhancement in arterial  phase of contrast,  32(45.7%) patients had rim enhancement, 2(2.9%) patients had calcification, 28(40.0%) patients had necrosis, 22(31.4%) patients had lymphadenopathy, 2(2.9%) patients  had portal vein invasion. It was observed that, 10(14.3%) patients had cyst and 20(28.6%) patients had abscess in benign cases. In malignant cases 14(20.0%) patients had HCC and 26(37.1%) patients had metastasis. Comparison of CT scan with cytopathology report of space occupying lesions in the liver shows true positive 40 cases, false positive 4 cases, false negative none and true negative 26 cases. It was observed that, sensitivity 100.0%, specificity 86.7%, accuracy 94.3%, positive predictive value 90.9% and negative predictive value 100.0%.Conclusion: In this study the cytopathological diagnosis of space occupying lesion in the liver significantly correlated with Computed Tomography (CT). Considering the high validity parameter it can be concluded that CT scan is a useful diagnostic modality for the diagnosis of space oc- cupying lesions in the liver.JCMCTA 2020 ; 31 (2) : 115-121